Species Richness of Arboreal Beetle in Suranadi Nature Park Area and Its Potential as a Source of Science Learning in Elementary Schools - Mohammad Liwa Ilhamdi; Muhammad Syazali (Jurnal Biologi Tropis, 2022)
The beetle data in Suranadi Nature Park is still limited to species that move on the ground. This study aims to analyze: (1) the species richness of the arboreal beetle, and (2) its potential as a science learning resource in elementary schools. This type of research is descriptive research using a qualitative approach. Sampling was carried out on the type of habitat in Suranadi Nature Park, namely the forest area with rice fields and residential areas, air flow and the middle with a dense canopy. The collected samples were identified to determine the species. The richness of this species data is then analyzed qualitatively to determine its potential as a source of science learning in elementary schools. This is done by comparing the species richness data of beetles and elementary thematic books, then the topics are assessed according to their level. The results showed that the species richness of arboreal beetles in Suranadi Nature Park consisted of 19 species from 5 families. The species are Lema sp., Aulacophora similis, Aulacophora quadrimaculata, Aulocophora sp.1, Aulocophora sp.2, Aulocophora sp.3, Aulocophora sp.4, Aulocophora sp.5 Parchicola sp., Podontia sp., Altica cyanea and Lilioceris sp. (family Chrysomelidae), Mimela sp., Mimela langbianica (Rutelidae), Exopholis hypoleuca, Ontophagus taurus, Protaetia fruhstorferi (Scarabaeidae) and Leptura sp. (family Cerambycidae). This arboreal beetle species data may be used as a source for elementary science learning on 33 sub-themes. Of this number, there are two sub-themes that have very appropriate categories, namely Sub-theme 2 The diversity of living things in my environment and Sub-theme 1 Components of the ecosystem.